An introduction to derivatives and risk management - Chance, Don M. (Australia : South-Western / Thomson Learning, 2001)
Business
2003-04-22
Keywords: Derivatives; Risk management; Pricing; Foreign currency derivatives; Interest rate derivatives; Financial risk management